The protocadherin 11X/Y gene pair as a putative determinant of cerebral dominance in Homo sapiens. (July 2009) - Priddle, Tom H; Crow, Tim J
The cerebral torque, a bias from right frontal to left occipital across the anterior––posterior axis is arguably the defining feature of the human brain, and the foundation for language. What is its genetic basis? Handedness and anatomical data suggest that this torque is specific to humans relative to the extant great apes. Asymmetry deficits associated with sex chromosome aneuploidies implicate loci on both the X and Y chromosomes. A block from the Xq21.3 band was duplicated to the Y chromosome 6 million years ago (close to, and a possible cause of the chimpanzee/hominin separation) containing the human-specific gene pair PCDH11X/Y . PCDH11Y has been subject to positive selection through hominin evolution including 18 amino-acid changes to the longest isoform of the protein. The PCDH11X protein has been subject to five substitutions including two cysteines in the ectodomain. The gene pair can account for sex differences, for example, in cerebral asymmetry and language.